Advancing Air Quality Management: A Comprehensive Review of UV Technology, Pyrolysis, and Their Integration (OODBODHAN, 2025)
Air pollution is a significant global issue, with pollutants like fine particulate matter (PM2.5), volatile organic compounds (VOCs), nitrogen oxides (NOx), and sulfur oxides (SOx) posing severe health risks. Combining ultraviolet (UV) technologies with pyrolysis has emerged as a promising control strategy, based on a literature review of peer-reviewed journals, industrial documents, and scholarly papers. UV-based technologies like photocatalytic oxidation (PCO), vacuum ultraviolet (VUV), and deep-ultraviolet (deep-UV) use reactive oxygen species (ROS) to break down pollutants. Pyrolysis transforms waste such as plastics, biomass, and medical waste into synthesis gas (syngas) and biochar with less toxic emissions. Integrating UV radiation with pyrolysis forms a hybrid system where photochemical reactions lower activation energies, increase pollutant degradation efficiency, and enable lower-temperature operation. This paper analyzes mechanisms, reactor configurations, and kinetic improvements, along with challenges like residual ozone generation (secondary pollutant), catalytic deactivation, and high energy consumption. Solutions include advanced reactor designs, cost-efficient UV sources, and hybrid catalytic materials. UV-enhanced pyrolysis is a cost-effective, adaptable method for reducing air pollution. Future research should optimize reaction conditions, develop integrated systems for industrial use, and conduct economic feasibility studies.